Is the effect of high voltage transmission lines undervalued?. Issue 2 (3rd April 2017) - Callanan, Judith
Abstract : Purpose: The purpose of this paper is to determine whether the discount placed on high voltage overhead transmission lines is underestimated. Design/methodology/approach: A quantitative analysis was undertaken, using a high voltage overhead transmission line (HVOTL) case study, to determine the effect on property values prior and post removal of the HVOTL structure. Sales data and demographics are compared to determine the change in neighbourhood characteristics. Findings: The results show that while the HVOTL is in place, the impact on value is confined to those properties in close proximity. This is in contradiction to the findings, where on removal of the HVOTL, the property values of the whole neighbourhood improve significantly. Research limitations/implications: The implication of this research is that property valuers (appraisers) need to change the way they take into account the presence of HVOTLs when valuing property, with more emphasis, being placed on the neighbourhood rather than just the properties in close proximity. While the HVOTL was in place, only properties in close proximity were negatively affected, but on removal of the HVOTL the whole neighbourhood increased in value. Originality/value: Results expand on current knowledge by demonstrating the difference between the discount rate that the valuers apply to the presence of the HVOTL, as compared to the positive impact to the whole neighbourhood on removal of the HVOTL.